2015
DOI: 10.11646/phytotaxa.222.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Mallomonas alpestrina sp. nov. (Synurales, Chrysophyceae, Stramenopiles) and its spineless relatives—Mallomonas alata group

Abstract: In this paper, we define the Mallomonas alata group and describe M. alpestrina sp. nov. from an oligotrophic high mountain glacial lake on the slopes of Haba Xue Shan (Haba Snow Mountain), China. The Mallomonas alata group is excluded from the M. pumilio group primarily based on the approximately triangular shape of the collar scales, the small hook-like protruded dome, and one considerably broader anterior flange of the body scale. We extend previous research on small species from the section Torquatae with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Nevertheless, they are at present far less reported from low latitude areas, as most of the stomatocysts are reported from temperate and cold zones. During the survey of silica scaled chrysophytes from tropical and subtropical areas, such as southern China (Wei et al 2013(Wei et al , 2014Nĕmcovà et al 2015), Vietnam (Gusev & Martynenko 2022;Gusev et al 2015Gusev et al , 2016Gusev et al , 2017Gusev et al , 2018Gusev et al , 2019Gusev et al , 2020Gusev et al , 2021, Indonesia (Kapustin et al 2019) and Cameroon (Piatek & Lukaszek 2016), more and more new species were reported. It confirmed that mountain lakes and generally water bodies in poorly studied tropical and subtropical areas from East Asia are rich with chrysophytes and many new species can be found there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, they are at present far less reported from low latitude areas, as most of the stomatocysts are reported from temperate and cold zones. During the survey of silica scaled chrysophytes from tropical and subtropical areas, such as southern China (Wei et al 2013(Wei et al , 2014Nĕmcovà et al 2015), Vietnam (Gusev & Martynenko 2022;Gusev et al 2015Gusev et al , 2016Gusev et al , 2017Gusev et al , 2018Gusev et al , 2019Gusev et al , 2020Gusev et al , 2021, Indonesia (Kapustin et al 2019) and Cameroon (Piatek & Lukaszek 2016), more and more new species were reported. It confirmed that mountain lakes and generally water bodies in poorly studied tropical and subtropical areas from East Asia are rich with chrysophytes and many new species can be found there.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the area is home to more than 20% of all higher plants and more than 25% of all animal species in China. Despite this high diversity in flora and fauna, only four chrysophyte species have been reported so far from this area (Shi et al 1994;Nĕmcovà et al 2015).…”
Section: Introductionmentioning
confidence: 99%